(untitled) - Sense, Andrew (New York, 2007)
Drawing on new research this book offers an entirely fresh perspective on how to cultivate learning within a project environment. It provides a framework to facilitate project practitioners' systematic reflection on their learning activities and to assist them in building a project learning practice. It also identifies new points of interest for researchers to further investigate the learning phenomenon in projects. This book weaves together diverse theories and empirical data in a way that should appeal to a wide academic and practitioner audience, and challenges all readers to consider intra-project learning as primarily a social activity which requires their deliberate commitment, understanding and attention.
Keywords: Project management,Employees,Organizational learning,Quản lý dự án,Nhà tuyển dụng,Học tập tổ chức; Training of,Tập huấn